Produce a hollowblock using coconut coir / Nur Syazwani Johar and Azamuddin Husin - Johar, Nur Syazwani; Husin, Azamuddin (2023)
To reduce negative environmental effect, the construction sector is facing increasing pressure to adopt sustainable and eco-friendly techniques. This study explores the inclusion of coconut coir, a natural and renewable resource, into hollow cement blocks to improve structural integrity and insulating properties. The research encompasses the design, assembly of a prototype, and thorough performance assessment of the coconut coir-infused hollow cement blocks. With growing recognition of environmental sustainability, there is an increase of interest in eco-friendly building materials. This study examines the use of coconut coir, a renewable and biodegradable component, in the production of hollow cement blocks. The research entails the formulation of an appropriate mix design, creation of hollow blocks with various concentrations of coconut coir, and assessment of their mechanical characteristics and environmental effects. The results show that the addition of coconut coir improves the block’s strength, reduces its weight, and improves thermal insulation. This suggests that coconut coir can be used as a sustainable alternative in the construction industry.